(untitled) (Bangladesh Journal of Medicine, 2025)
Background: Pneumonia causes significant child morbidity and mortality globally, especially in developing countries. Hypoxemia is a critical complication in pediatric pneumonia and a key indicator of severe disease needing urgent medical intervention. This study aimed to investigate the clinical predictors of hypoxemia in children with pneumonia. Methods: This is a cross-sectional comparative study was conducted at Sir Salimullah Medical College & Mitford Hospital, Dhaka, Bangladesh, from January to December 2022. A total of 394 children aged 2-59 months with pneumonia were purposively enrolled. Of these, 132 (33.5%) had hypoxemia, while 262 (66.5%) did not. All demographic, diagnostic, and clinical data were recorded and analyzed usingSPSS version 22.0. Results: In univariate analysis, hypoxic status correlated significantly with vomiting, fast breathing, inability to drink, unusual sleepiness(p<0.05), unconsciousness / lethargy, immobility during examination (p<0.001),abnormal sleepiness, and palm pallor(p<0.05). Indicators included nasal flaring, chest indrawing, head nodding, continuous grunting, diminished breath sounds (p<0.05),and heart rate (p<0.001)..Sensitivity was higher for heart rate, fast breathing, palm pallor, and chest indrawing. Specificity was higher for vomiting, lethargy/unconsciousness, unusual sleepiness, head nodding , grunting, and nasal flaring. Conclusion: Among children with pneumonia, nearly one-third may behypoxic, with a higher frequency in females. Sensitivity for predictors of hypoxemia is better in fast breathing, pallor of the palm, lower chest indrawing, and increased heart rate. Specificity is better in persistent vomiting, lethargy, unusual sleepiness, head nodding, grunting, and nasal flaring. Bangladesh. Bangladesh J Medicine 2025; 36(3): 129-135